Pengaruh Pola Asuh dan Persepsi terhadap Kepercayaan Diri Siswa Madrasah Ibtidaiyah yang Bermain Roblox - Ahmad Fatkhus Syahdani; Lucia Rini Sugiarti; Erwin Erlangga (Assyfa Journal of Islamic Studies, 2026)
The rapid advancement of digital technology has made online games such as Roblox an inseparable part of children’s lives. Nevertheless, its impact on students’ psychological development, particularly self‑confidence, remains underexplored in the context of Islamic education. This study aims to analyse the predictive relationship of parenting style and perception of Roblox with the self‑confidence of students who play Roblox at MI Miftahul Huda Tebing Suluh. A quantitative approach with an explanatory design was employed, involving 121 students from grades I to V as the sample. Data were collected using Likert‑scale questionnaires and analysed using multiple linear regression. The results show that parenting style has a significant positive relationship with students’ self‑confidence (β = 0.203; p = 0.010). Furthermore, perception of Roblox also shows a significant positive relationship, contributing even more dominantly (β = 0.569; p < 0.001). Simultaneously, both variables significantly predict students’ self‑confidence (R² = 0.487; F = 56.029; p < 0.001). The uniqueness of this study lies in integrating parenting style and digital perception as simultaneous predictors of self‑confidence within the Madrasah Ibtidaiyah context. These findings have practical implications for parents and educators in fostering children’s self‑confidence in the digital era.